Removal of Acid Black 194 Dye from Water by Electrocoagulation with Aluminum Anode - (:unkn) unknown (TAYLOR & FRANCIS INC, 2016)
Application of an electrocoagulation process (EC) for the elimination of AB194 textile dye from synthetic and textile wastewater (effluent) contaminated with AB194 dye, was carried out using aluminum anodes at two different initial pH values. Tafel studies in the presence and absence of the dye were performed. The aluminum species formed during the electrolysis were quantified by atomic absorption, and the flocs formed in the process were analyzed by HPLC-MS. Complete removal of AB194 from 1.0 L of solution was achieved applying low densities current at initial pH values of 4.0 and 8.0. The removal of AB194 by EC was possible with a short electrolysis time, removing practically 100% of the total organic carbon content and chemical oxygen demand. The final result was completely discolored water lacking dye and organic matter. An effluent contaminated with 126 mg L-1 AB194 dye from a Chilean textile industry was also treated by EC under optimized experimental conditions, yielding discolored water and considerably decreasing the presence of organic compounds (dye + dyeing additives), with very low concentrations of dissolved Al3+. Analysis of flocs showed the presence of the original dye without changes in its chemical structure.